Differential Mortality and High Viral Load in Naive Pacific Oyster Families Exposed to OsHV-1 Suggests Tolerance Rather than Resistance to Infection - M. Victoria Agnew; Carolyn S. Friedman; Christopher Langdon; Konstantin Divilov; Blaine Schoolfield; Benjamin Morga; Lionel Degremont; Arun K. Dhar; Peter Kirkland; Brett Dumbauld; Colleen A. Burge (Pathogens, 2020)
Pacific oysters, Crassostrea gigas, are one of the most productive aquaculture species in the world. However, they are threatened by the spread of Ostreid herpesvirus-1 (OsHV-1) and its microvariants (collectively “µvars”), which cause mass mortalities in all life stages of Pacific oysters globally. Breeding programs have been successful in reducing mortality due to OsHV-1 variants following viral outbreaks; however, an OsHV-1-resistant oyster line does not yet exist in the United States (US), and it is unknown how OsHV-1 µvars will affect US oyster populations compared to the current variant, which is similar to the OsHV-1 reference, found in Tomales Bay, CA. The goals of this study were to investigate the resistance of C. gigas juveniles produced by the Molluscan Broodstock Program (MBP) to three variants of OsHV-1: a California reference OsHV-1, an Australian µvar, and a French µvar. This is the first study to directly compare OsHV-1 µvars to a non-µvar. The survival probability of oysters exposed to the French (FRA) or Australian (AUS) µvar was significantly lower (43% and 71%, respectively) than to the reference variant and controls (96%). No oyster family demonstrated resistance to all three OsHV-1 variants, and many surviving oysters contained high copy numbers of viral DNA (mean ~3.53 × 108). These results indicate that the introduction of OsHV-1 µvars could have substantial effects on US Pacific oyster aquaculture if truly resistant lines are not achieved, and highlight the need to consider resistance to infection in addition to survival as traits in breeding programs to reduce the risk of the spread of OsHV-1 variants.